(untitled) (Research, Society and Development, 2020)
The research aimed to identify in the scientific literature the factors associated with the burden of the family caregiver of elderly people with Alzheimer’s disease and to investigate the relationship between the conditions and circumstances in which care is provided and its impact on the caregiver’s life. The present work is a qualitative study of Bibliographic Review of the type Integrative Review. The research was carried out by analyzing the publications selected in the online databases, MEDLINE, LILACS and BDENF indexed in the Virtual Health Library (VHL) using a form structured in two axes. The search for the material occurred through the PICo strategy. Twenty-four studies were reviewed, which were grouped by semantic similarity, generating two categories, 1. Challenges experienced by family caregivers of elderly people with Alzheimer’s disease and factors associated with care overload, and 2. Biopsychosocial repercussions of the care given to elderly people with Alzheimer’s disease. Alzheimer’s in the family caregiver’s life. The study made it possible to identify several factors associated with overload in family caregivers of elderly people with AD, among them the lack of social and professional support, lack of knowledge, increased amount and severity of neuropsychiatric symptoms of Alzheimer’s in the elderly and workload, when factors are not properly controlled and mediated, caregivers suffer negative impacts on their physical, psychosocioemotional and financial health. It is necessary to create public policies in order to control the factors that generate burden and the negative repercussions of care in the life of the family caregiver of elderly people with Alzheimer’s.